Prevalence of Depression in Patients with Spondyloarthritis and Its Impact on Disease Activity: A Cross-Sectional Study: Depression in Patients with Spondyloarthritis and Its Impact on Disease Activity - Lal, Tarmim; Din, Zia Ud; Khan, Medrar Ullah; Rabbani, Farah; Shah, Syed Raheel Ali; Fahad, Muhammad; Shah, Syed Yar Muhammad (Pakistan Journal of Health Sciences, 2026)
Spondyloarthritis refers to a chronic inflammatory rheumatic disorder that is characterized by pain, disability, and poor quality of life, potentially predisposing the affected patients to psychological comorbidity, including depression. Depression can hurt disease activity, treatment response, and clinical outcomes, but the burden has not been well acknowledged in clinical practice among patients with spondyloarthritis. Objective: To find the prevalence of depression in patients with spondyloarthritis (SpA) and to identify the association of depression with disease activity. Methods: A cross-sectional study was carried out in the Department of Rheumatology, Lady Reading Hospital, Peshawar, Pakistan. Adult patients who had verifiable cases of SpA were recruited in the study in six-month consecutive intervals between 1st February and 31st July 2025. Depression status was used to stratify the participants, and pertinent statistical tests were used to evaluate associations of normally and non-normally distributed variables. Independent t-test, Mann-Whitney U, and chi-square tests were used. Any p-value less than 0.050 was taken as statistically significant. Results: The prevalence of depressive symptoms in 323 spondyloarthritis patients was 51.1% with mild and moderate depression. Disease activity (BASDAI), inflammatory markers (ESR, CRP), and disease duration of depressed patients were considerably higher than those of non-depressed patients (p<0.050). Conclusions: Depression is very common among patients living with spondyloarthritis and is characterized by higher disease activity, systemic inflammation, and longer duration of disease, thereby supporting the importance of screening mental health during clinical care.